Strategi Peningkatan Pembiayaan Multi Guna (PMG) Pada PT. Bank Sumut Unit Usaha Syariah - Harsono, Muhammad; Soemitra, Andri; Arif, Muhammad (ITB AAS INDONESIA Surakarta, 2023)
Improper financing management will cause many problems and will even cause the collapse of Islamic banks. In financing carried out by Islamic banking, there are bound to be many obstacles experienced, such as default constraints, problematic financing or other constraints, especially during the Covid 19 pandemic. To minimize the various obstacles faced earlier, of course, Islamic banking is required to have an accurate strategy to win market competition while minimizing the occurrence of problem financing. This study aims to analyze the strategy of PT. Bank Sumut Sharia Business Unit in increasing Multipurpose Financing (PMG). This research is a type of qualitative research. Obtained research results SWOT analysis results show that the company's position is in quadrant 1, namely supporting an aggressive strategy. This quadrant position is a very favorable situation, where the company has opportunities and strengths so that it can take advantage of existing opportunities. The strategy that must be applied in this condition is the SO (Strength - Opportunity) Strategy, which is a strategy that utilizes the company's internal strengths to take advantage of external opportunities. The S-O strategy is developed by combining strengths in the internal evaluation matrix and opportunity factors in the external evaluation matrix.